Technopreneurship Module - Noor Azlinna, Azizan; Mazita, Mokhtar; Azizan, Azit; Ida Rizyani, Tahir; Siti Airin, Abdul Ghani; Wan Khairul Anuar, Wan Abdul Manan (Pusat Keusahawanan, Universiti Malaysia Pahang, 2015)
This course intends to provide an understanding of fundamentals of entrepreneurship. The topics covered include assessing economic environment for new business ventures, application of technology in entrepreneurship, rules and regulations governing business entities in Malaysia, financial assistances and technical supports from various agencies, developing business plan, marketing plan, business operational plan and financing plan. Students will be exposed to various case studies on successful entrepreneurs, locally and internationally.